Study of Incongruence in the Implementation of Language Policy from Pancasila Perspective - Azizah, Dinar Martia (Soegijapranata Catholic University, 2024)
The goal of this study is to describe the incongruence in the implementation of language policy from Pancasila perspective. This research is a content analysis. The data in this research are in the forms of words, sentences, and pictures. The data collecting technique in this research employs document study. The results of this research show that the incongruity in the implementation of language policy from Pancasila perspective is reflected in various fields, including politics, economics, and social cultural. This happens in numerous cases, including the implementation of international standard education, the elimination of Indonesian language subject at Jakarta International School, the use of English in nation speech, and the elimination of obligation for foreign workers to understand Indonesian language. The implications of this research are the revitalization of Pancasila’s values in the process of policies formulation and implementation both vertically and horizontally and involve makers at the macro, meso and micro. Therefore, recommendations of language policy which are aligned with Pancasila values which can be explored more in further research